Effect of Live Yeast (Saccharomyces cerevisiae) Feeding on Milk Composition and Gross Profit Margin of Crossbred Dairy Cattle at Khumaltar, Nepal - Acharya, B.; Dhital, B.; Paudel, T. P.; Sah, A. K.; Kaphle, K. (Journal of the Institute of Agriculture and Animal Science, 2020)
This study was carried out to assess the effect of live yeast Saccharomyces cerevisiae (NutrifermTM) inclusion in feed and its effects on milk composition and gross profit-margin from crossbred dairy cattle at Khumaltar, condition. An Experiment was carried out at National Cattle Research Program station of Nepal Agriculture Research Council (NARC), Khumaltar, Lalitpur of Nepal for 28 days from 19 March 2015 to 15 April 2015. Twenty crossbred cattle were selected randomly and divided into five treatment groups with each, group having four cows arranged in Complete Randomized Design (CRD). Five type of ration was composed to experimental animals; T1 : 0.5kg/MT, T2: 1 kg/MT, T3: 1.5 kg/MT, T4 : 2 kg/MT and T5 as control. Milk samples were collected during milking and Lactoscan auto analyzer was used to measure fat, solid not fat (SNF), lactose, protein along with the volume for four weeks’ experimental period. Data was analyzed using Split plot ANOVA method. Mean fat percentage between treatments was found non-significant but there was significant difference (P<0.05) in mean fat percentage across different time periodS in day 1st and 28th day being statistically significant. In this experiment, changes SNF, protein, and lactose in milk were found to be non-significant. Gross profit-margin of the milk production was done with the market price of raw milk and it was found to be significant (P<0.05) for 1st and 28th days of experiment. Supplementation of liveyeast Saccharomyces cerevisiae (NutrifermTM) @ 2 kg/ 1000 kg feed with standard feeding diet enhanced the milk production, improved fat content in milk and generate profit margin.